Combined Minimally Invasive Redo Mitral Surgery and Pectus Excavatum Correction. Issue 7 (7th May 2015) - Vola, Marco; Grinberg, Daniel; Azarnoush, Kasra; Lopez, Manuel; Favre, Jean‐Pierre; Tiffet, Olivier
Abstract We present a technique of mitral valve surgery performed in a patient with severe pectus excavatum and previous Bentall surgery. Neither redo sternotomy nor conventional right minithoracotomy were thought to provide adequate surgical access to the mitral valve. We therefore opted for a combined procedure comprising sternal reconstruction and right minithoracotomy mitral valve replacement. The mitral valve was replaced and the sternum reconstructed according to the Ravitch technique. doi: 10.1111/jocs.12559 (J Card Surg 2015;30:570–573)